2022
DOI: 10.3389/fcvm.2022.889554
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Hypertension-Mediated Organ Damage in Hypertensive Urgencies and Hypertensive Outpatients

Abstract: BackgroundThe prevalence of hypertension mediated organ damage (HMOD) in patients attending the Emergency Department (ED) with symptomatic blood pressure (BP) rise is unknown, and whether HMOD varies between asymptomatic and symptomatic patients with grade 3 hypertension is unclear.AimThis study aimed to investigate cardiac and vascular HMOD in hypertensive urgencies (HU) and asymptomatic outpatients with grade 1–3 hypertension.MethodsPatients attending the ED with a symptomatic BP rise ≥180/110 mmHg were pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…At 72 h visit, patients with uncontrolled BP had worse PWV, suggesting a possible role of aortic stiffness in impeding proper BP control, or possibly grater vascular damage in patients with short-term uncontrolled BP. A recent study showed that HU patients had subclinical HMOD profile midway between patients with asymptomatic grade 3 hypertension and patients with various grade hypertension, matched for office BP [ 50 ]. The higher prevalence of subclinical HMOD in HE patients found in the present study underlines that HE patients have worse baseline CV risk profile than HU patients, leading to more severe manifestations of acute BP rise.…”
Section: Discussionmentioning
confidence: 99%
“…At 72 h visit, patients with uncontrolled BP had worse PWV, suggesting a possible role of aortic stiffness in impeding proper BP control, or possibly grater vascular damage in patients with short-term uncontrolled BP. A recent study showed that HU patients had subclinical HMOD profile midway between patients with asymptomatic grade 3 hypertension and patients with various grade hypertension, matched for office BP [ 50 ]. The higher prevalence of subclinical HMOD in HE patients found in the present study underlines that HE patients have worse baseline CV risk profile than HU patients, leading to more severe manifestations of acute BP rise.…”
Section: Discussionmentioning
confidence: 99%
“…An increased interventricular septum thickness can indicate hypertension‐mediated target‐organ damage in the heart, and is a commonly reported outcome in clinical practice. 50 , 51 The European Society of Cardiology/European Society of Hypertension recommends the assessment of interventricular septum thickness in patients with hypertension, as a reduction in blood pressure levels leads to a regression of interventricular septum thickness and LV hypertrophy, with a consecutive decrease in cardiovascular disease risk. 52 In the current analysis, the extensive reduction in systolic blood pressure could help explain the significant decrease in interventricular septum thickness; however, the decrease in interventricular septum thickness appears to be independent of blood pressure or antihypertensive medication (Figure 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension urgencies were defined as acute elevation of blood pressure (usually systolic blood pressure (SBP)>180mmHg and/or diastolic blood pressure (DBP)>110mmHg) without impairment of target organ function. 10 Exclusion criteria included patients with primary renal insufficiency, valvular heart disease, and metabolic diseases. Patients with allergies to the drugs administered in this study were also excluded.…”
Section: Methodsmentioning
confidence: 99%